ONE YEAR OUTCOME OF STRUCTURED DIABETES MELLITUS EDUCATIONAL PROGRAM (SDEP) ON THE MANAGEMENT OF DIABETES IN APRIMARY CARE CLINIC - K, Nor Azam; B, Bustamanizan; Z, Asyikin; P, Hafizah (International Journal of Allied Health Sciences, 2023)
Introduction: Health education may empower the patient in term of reinforcing belief, medication adherence and initiating lifestyle changes. This study aims to examine the benefit of SDEP on the management of diabetes mellitus in a health clinic. Materials and method: The SDEP are a program targeted at poorly controlled diabetic patients. It is a half day program with 5-6 participants, consisting of interactive and practical sessions by doctor, diabetes educator, nutritionist, occupational therapist, and pharmacist. Based on the diabetes record book of patients who had participated in 2017 and 2018, only 35 participants have a complete record, thus were included in this study. All relevant information pre and one-year post program were obtained and analysed with SPSS. Results: All participants were Malay FELDA settlers with the mean age of 60+7. The mean HbA1c level at pre-program was 9.8%. There was a significant reduction in mean HbA1c level of 1.2% one-year post program. There were no new incidence of co-morbidities and diabetic complications or significant changes in other clinical parameters among this group. There was also no significant difference in total dose/day of diabetic treatment (OHAs, insulin) between pre and 1-year post-program. Conclusion: Diabetic education program, which is targeted, structured, interactive and multi-disciplinary in nature has shown to be beneficial for diabetes mellitus management without the need for intensification of therapy.